Bad mothers and maternal ambivalence in Ciclul Hallipilor [The Hallipa cycle] by Hortensia Papadat-Bengescu and Patimi [Passions] by Sofia Nădejde - Moroșan, Ioana (Swedish Journal of Romanian Studies, 2026)
The article analyzes the symptomatic representations of maternal experience in the modern Romanian novel written by women. It aims to draw attention to maternal voices portrayed in literary texts across national contexts at the beginning of the 20th century. The two novels proposed for this study focus on two prominent Romanian women writers who held ideologically opposing views: Sofia Nădejde (1856-1946), a feminist and socialist activist, and Hortensia Papadat-Bengescu (1876-1955), a well-established female novelist associated with the influential literary group which marked Romanian literary modernism during the interwar period – Sburătorul. This article examines the instrumental role of maternity and maternal ambivalence in these two novels. The often distant or even toxic relationship between mothers and children illustrates that maternity in this context is not a choice, but a question influenced by social demands and “female responsibility.” Thus, I explore significant aspects of “modern motherhood” as a gendered experience shaped by the social order: maternity as a matrimonial transaction, domestic oppression, social pressure, and finally, how the need for social emancipation and economic advancement interfere with the maternal role that women experience in terms of patriarchal constraints. This article aims to reflect on how these novels depict maternity as an experience beyond women’s agency.